Integrating Network Pharmacology and Experimental Verification to Explore the Pharmacological Mechanisms of Cordycepin against Pulmonary Arterial Hypertension in Rats - Lin, Jiangpeng; Zhang, Yuzhuo; Lin, Shuangfeng; Ding, Haiming; Liu, Weihua (Combinatorial Chemistry & High Throughput Screening, 2024)
BackgroundPulmonary Arterial Hypertension (PAH) is a fatal disease with high morbidity and mortality. Cordycepin has anti-inflammatory, antioxidant and immune enhancing effects. However, the role of Cordycepin in the treatment of PAH and its mechanism is not clear.MethodsThe Cordycepin structure and PAH-related gene targets were obtained from public databases. The KEGG and GO enrichment analysis of common targets was performed in DAVID. PPI networks were also mapped using the STRING platform. AutoDock Vina, AutoDockTools, ChemBio3D and Pymol tools were selected for molecular docking of key targets. The therapeutic effects of Cordycepin on PAH were observed in Monocrotaline (MCT)-induced PAH rats and platelet-derived growth factor BB (PDGFBB)-induced rat pulmonary artery smooth muscle cells (PASMCs). The right ventricular systolic pressure (RVSP) was detected. HE staining, Western Blot, Scratch assay, EDU and TUNEL assays were used, respectively.ResultsThrough Network Pharmacology and molecular docking, the Cordycepin-PAH core genes were found to be TP53, AKT1, CASP3, BAX and BCL2L1. In MCT-induced PAH rats, the administration of Cordycepin significantly reduced RVSP, and inhibited pulmonary vascular remodeling. In PDGFBB-induced PASMCs, Cordycepin reduced the migration and proliferation of PASMCs and promoted apoptosis. After the Cordycepin treatment, the protein expressions of TP53, Cleaved CASP3 and BAX were significantly increased, while the protein expressions of p-AKT1 and BCL2L1 were significantly decreased in MCT-PAH rats and PDGFBB-induced PASMCs.ConclusionThis study identified that TP53, AKT1, CASP3, BAX, and BCL2L1 were the potential targets of Cordycepin against PAH by ameliorating pulmonary vascular remodeling, inhibiting the abnormal proliferation and migration of PASMCs and increasing apoptosis of PASMCs. which provided a new understanding of the pharmacological mechanisms of Cordycepin in the treatment of PAH.
Keywords: Cordycepin